ANALISIS POLA PERILAKU GENDER PADA MASYARAKAT KELAYU KABUPATEN LOMBOK TIMUR - Baiq Fitri Rahmawati (Educatio, 2014)
The aims of study is to describe the pattern of gender behavior in Kelayu society by comparing patterns of gender behavior in housewifeâ€™s family with mother workâ€™s family, and to analyze the differences between them. The method of research use a qualitative method with the techniques of data collection such as interviews, observation and documentation. Meanwhile, the techniques of data analysis used  Milles and Hubbermanâ€™s  techniques is data reduction, data display, dan  conclusion drawing/verification. The results of this study showed a pattern of gender behavior in society Kelayu as follows: (1) Men are the breadwinners and women are housekeeper. (2) Aggressiveness is male. With the aggressive nature allows men to access the wealth and social status in the community; (3) Respect and obedience of the woman. Women are required to have a high adherence properties, especially adherence to her husband and their parents.; (4) a high activity level is male. Men have a higher level of activity than women, since small socialized in the forms of the game. They do a lot of outdoor activities, such as playing the game wide cap pistol, kites, and many other activities that require a lot of motion and outside the home; and (5) Women have a passive nature and soft, gentle and loving, so it is reasonable given the task of parenting. Weak women makes it requires protection from men. Keywords: behavioral patterns of gender, ancestry housewife, mother's family work